Serum MIC-1, LMTK-3 and IGFBP-7 levels in the prognosis of lung cancer treated with ablation combined with chemotherapy: Serum MIC-1, LMTK-3 and IGFBP-7 levels in lung cancer - Fu, Yilin; Shi, Lifeng; Lu, Quanxin; Yu, Fatao; Hong, Xiaofeng; Zeng, Guoliang; Li, Meng (Journal of Medical Biochemistry, 2025)
Objective To explore the value of the serum levels of macrophage inhibitory factor 1 (MIC-1), Lemur tyrosine kinase 3 (LMTK-3), and insulin-like growth factor binding protein 7 (IGFBP-7) in the prognosis assessment of patients with advanced lung cancer treated with ablation combined with chemotherapy.Methods 190 patients with advanced lung cancer who received care at this hospital between January 2022 and June 2024 were chosen to be part of the lung cancer group. The healthy control group consisted of 90 healthy people who attended the hospital and had physical tests over the same time period. Percutaneous microwave thermal ablation treatment was used to treat every patient with advanced lung cancer, and chemotherapy was administered within one week after treatment. The levels of serum MIC-1, LMTK-3 and IGFBP-7 before and after treatment and before treatment in patients with different therapeutic effects in the lung cancer group and the healthy control group were compared. Univariate and multivariate analyses were conducted on the factors affecting the prognosis of patients to analyze the efficacy of serum MIC-1, LMTK-3 and IGFBP-7 levels in predicting the prognosis of patients with advanced lung cancer.Results Serum MIC-1 and LMTK-3 levels in the lung cancer group were substantially higher than those in the healthy control group both before and after therapy (P
Keywords: Macrophage inhibitory factor 1; Lemur tyrosine kinase 3; Insulin-like growth factor; Binding protein 7; Ablation; Advanced lung cancer